2003
DOI: 10.1107/s0108768103002477
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular structures of N 4-substituted 2,4-diamino-6-benzyloxy-5-nitrosopyrimidines

Abstract: The molecular and supramolecular structures of eight N(4)-substituted 2,4-diamino-6-benzyloxy-5-nitrosopyrimidines are discussed, along with one analogue containing no nitroso substituent. The nitroso derivatives all exhibit polarized molecular-electronic structures leading to extensive charge-assisted hydrogen bonding between the molecules. The intermolecular interactions include hard hydrogen bonds of N-H...O and N-H...N types, together with O-H...O and O-H...N types in the monohydrate of 2-amino-6-benzyloxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 15 publications
5
24
2
Order By: Relevance
“…The atoms marked with an asterisk (*) are at the symmetry position (2 À x; 2 À y; 1 À z). It is noteworthy that as found in several previous examples (Melguizo et al, 2003;Quesada et al, 2003Quesada et al, , 2004Low et al, 2007;Trilleras et al, 2007), the distortion from planarity of the pyrimidine rings does not seem to impair the development of polarized electronic structures. The overlap and resonance integrals involving neighbouring atoms, at their optimum in rings which are planar, are evidently diminished only modestly by ring puckering of the magnitude observed here.…”
Section: Figuresupporting
confidence: 72%
See 2 more Smart Citations
“…The atoms marked with an asterisk (*) are at the symmetry position (2 À x; 2 À y; 1 À z). It is noteworthy that as found in several previous examples (Melguizo et al, 2003;Quesada et al, 2003Quesada et al, , 2004Low et al, 2007;Trilleras et al, 2007), the distortion from planarity of the pyrimidine rings does not seem to impair the development of polarized electronic structures. The overlap and resonance integrals involving neighbouring atoms, at their optimum in rings which are planar, are evidently diminished only modestly by ring puckering of the magnitude observed here.…”
Section: Figuresupporting
confidence: 72%
“…While simply substituted pyrimidines generally exhibit effective planarity of the pyrimidine rings, we have found that where three contiguous substituents are present in the 4-, 5and 6-positions, the rings are sometimes quite markedly nonplanar, giving boat (Quesada et al, 2004;Low et al, 2007;Trilleras et al, 2007), twist-boat (Melguizo et al, 2003;Quesada et al, 2003) or screw-boat (Low et al, 2007) conformations, and comparison with less sterically congested analogues suggests that the steric clashes between neighbouring bulky substituents drive the ring distortion from planar to boat or twist-boat forms. However, it is striking that, even in compounds where the pyrimidine ring is distorted from planarity, the development of the polarized electronic structure does not seem to be significantly impaired by the distortion, as illustrated by examples such as (D) (Melguizo et al, 2003), (E) (Quesada et al, 2003) and (F) (Quesada et al, 2004).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The apparent simplicity found in the present series (I)-(IX), which may be sufficiently robust to be of predictive value, must be contrasted with the behaviour which we have previously observed in a number of other extended series of cognate structures (Glidewell et al, 2002(Glidewell et al, , 2004(Glidewell et al, , 2005(Glidewell et al, , 2006Melguizo et al, 2003;Quesada et al, 2004;Cuffini et al, 2006;Wardell et al, 2006Wardell et al, , 2007, where no one structure in any series could readily be predicted even from a detailed knowledge of each of the remaining structures in that series because, very commonly, no two structures in a given series manifested the same range of direction-specific intermolecular interactions. A significant source of unpredictability in the present series concerns the presence or absence of solvation in the crystal structure.…”
Section: Concluding Discussioncontrasting
confidence: 73%
“…Conjugated nitrosamines belong to the same family as the enols of b-diketones and other conjugated systems with intramolecular hydrogen bonds. Therefore, the formation of intramolecular hydrogen bonds may be expected, and indeed, such interactions were found in the solid-state structures of 3-amino-2-nitrosocyclohex-2-en-1-one [33], 5amino-4-nitrosopyrazole [33], and 6-amino-5-nitrosopyrimidines [34][35][36][37][38]. Our results are in agreement with those of Prochazkova et al reporting that a mixture of two forms with distinct hydrogen-bond patterns were found in the solutions of compounds with two hydrogen bond donors neighboring the nitroso group [32].…”
Section: Conformational and Electronic Studymentioning
confidence: 99%